2009
DOI: 10.1177/230949900901700310
|View full text |Cite
|
Sign up to set email alerts
|

Pulse-Lavage Brushing Followed by Hydrogen Peroxide-Gauze Packing for Bone-Bed Preparation in Cemented Total Hip Arthroplasty: A Bovine Model

Abstract: Pulse-lavage brushing is more effective at cleansing the femoral canal and increasing mechanical strength at the cement-bone interface than preparation with normal-saline irrigation or hydrogen peroxide-soaked gauze packing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…In addition, the killing ability of H 2 O 2 on pathogenic bacteria like Pseudomonas aeruginosa is doubtful because catalases are reported to exist in their bodies [55] . H 2 O 2 is also used regularly to prepare the bony bed in cemented arthroplasties as well as to achieve hemostasis in neurosurgery [56,57] . It is also an adjunct hemostatic to topical epinephrine in patients with known platelet dysfunction after burn excision [58] .…”
Section: Current Clinical Use Of Hydrogen Peroxidementioning
confidence: 99%
“…In addition, the killing ability of H 2 O 2 on pathogenic bacteria like Pseudomonas aeruginosa is doubtful because catalases are reported to exist in their bodies [55] . H 2 O 2 is also used regularly to prepare the bony bed in cemented arthroplasties as well as to achieve hemostasis in neurosurgery [56,57] . It is also an adjunct hemostatic to topical epinephrine in patients with known platelet dysfunction after burn excision [58] .…”
Section: Current Clinical Use Of Hydrogen Peroxidementioning
confidence: 99%
“…They found no reduction in blood loss following hydrogen peroxide application compared to controls 34. Another study on hydrogen peroxide hemostatic effects in an animal model also demonstrated no benefit versus conventional hemostatic techniques 35.…”
Section: Basic Sciencementioning
confidence: 97%
“…It is thought that its ability to mechanically remove debris (fats, marrow and blood clots) and haemostasis allows cement to interdigitate deeper and thus better quality of cementation. 8 Ackland conducted a study comparing the quality of cementation using different methods of femoral canal preparation; he used pulsatile lavage followed by H 2 O 2 gauze packing, pulsatile lavage with saline, H 2 O 2 gauze packing alone or saline irrigation alone. He was able to show that pulsatile lavage alone regardless of whether it was with or without H 2 O 2 had the most significant effect on the quality of cementation.…”
Section: Bone Cementationmentioning
confidence: 99%